Implementation of the Public Relations Function at the Secretariat of the Pati Regency House of Representatives - Iqbal Maulana Firdaus; Angga Intueri Mahendra (PT Mattawang Mediatama Solution, 2023)
As one of the government agencies in Indonesia, public relations within the scope of the Secretariat of the Regional People's Legislative Assembly of Pati Regency has an obligation to provide information related to policies, as well as with new regulations stipulated by members of the council. Public Relations itself has an important role and an important function as well in assisting a task from the government related to the delivery of information and mediation using various mass media and online media. The purpose of this study is to determine the implementation of the functions of a public relations officer within the scope of the Secretariat of the Regional People's Legislative Assembly of Pati Regency. The research method used in this research is descriptive by selecting an informant using a purposive sampling technique. The results of research from a public relations officer at the Secretariat of the Regional People's Legislative Assembly of Pati Regency are In this case it shows that the role according to the expert above shows that there are only three roles related to the functions and duties within the scope of public relations of the Pati Regency Dprd Secretariat, namely as a Communication Facilitator (Communication Facilitator). , As a Problem Solving Process Facilitator, and as a Communication Technician and expert advisors are not included because the public relations agency Secretariat of the Pati Regency Dprd is an institution that is still under the auspices of the Pati regional government where all responsibilities such as duties and the function is determined by the regional government of Pati. That way this institution does not stand alone but is still under the auspices of the Pati district government.